Operation Information System Pengaruh Bisnis Model, Bisnis Proses dan Struktur Organisasi Terhadap Sistem Informasi Operasi - Waluyo, Ponco (Jurnal Ekonomi Manajemen Sistem Informasi, 2023)
Abstract: The effect of Business Model, Business Process and Organization Structure on Operation Information System is a scientific article in the literature study within the scope of the field of science. The purpose of this article is to build a hypothesis of the influence between variables that will be used in further research. Research objects in online libraries, Google Scholar, Mendeley and other academic online media. The research method with the research library comes from e-books and open access e-journals. The results of this article: 1) Business Model has an effect on Operation Information System; 2) Business Process has an effect on Operation Information System; and 3) Organization Structure has an effect on Operation Information System